Contacting a public official: Concept and measurement in cross‐national surveys, 1960s–2010s. (1st June 2022) - Dubrow, Joshua K.; Tomescu‐Dubrow, Irina; Lavrinenko, Olga
Abstract: Background: In the digital age, contacting a public official is a direct, low‐cost means of influence, but most cross‐national surveys ignore it. Objective: We go in‐depth on "contact" to define it, present how it has appeared in major cross‐national surveys since the 1960s, and how survey respondents might understand it today. We then explore its popularity and determinants in Europe across time. Methods: We use the Survey Data Recycling project's Cotton File and the European Social Survey (ESS) 2002 and 2018. Results: Of nine major international survey projects that have this item, only ESS regularly includes it. Across Europe, the popularity of contact did not change much, and the factors that associate with generalized contact in 2002 are the same as in 2018. Conclusion: Data producers should test the meaning of contact among respondents and differentiate between generalized and particularized forms.